Effect of Butanol Extract of Maturated Mahkota Dewa (Phaleria macrocarpa) Fruit on Liver Tissue of Mice (Mus musculus) - ARIF SOEKSMANTO (Biodiversitas Journal of Biological Diversity, 2006)
Mahkota dewa (Phaleria macrocarpa [Scheff.] Boerl.) is a poisonous plant, but almost all parts of the plants can be used as a traditional medicine. Consuming the plant directly can cause swollen, sprue, numb at tongue, fever, even unconscious. Although the plant can conquere various diseases, from diabetes mellitus, hemorrhoid, impotency to cancer, but research on the plant is still limited. A research was conducted to find out effect of subchronic dosage of butanol extract of maturated mahkota dewa fruit. Observation was carried out on liver tissue which is main organ detoxifying poison in the body. Dosage of butanol extract of 0; 42,5; 85 and 170 mg/kg body weight was administered intra peritoneally to mice. The result showed that butanol extract of maturated mahkota dewa fruit did not affect liver tissue, although at dosage 170 mg/kg body weight, a vacuolization on liver's tissue, was occurred.Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: Phaleria macrocarpa, mahkota dewa, plant extract, mice, Mus musculus, liver, vacuolization